2011
DOI: 10.1027/1614-0001/a000033
|View full text |Cite
|
Sign up to set email alerts
|

Gender Influences on the Work-Related Stress-Coping Process

Abstract: The increasing incidence of occupational stress is recognized as a global phenomenon that is having a detrimental impact on both individuals and organizations. This study aims to identify whether men and women adopt different stress and coping processes when subjected to stress in a work context. A total of 258 workers of various professions (males = 106, females = 152) participated in the study. Results indicated that men and women differ in their stress and coping processes, forming two very distinct groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
1
23
0
2
Order By: Relevance
“…Another important implication that is apparent in these results is that men and women cope with work stressors in different ways. As predicted by social role theory (Eagly, ), it appears that society places pressure on both men and women to cope with stressors in different ways (e.g., Feingold, ; Watson, Goh, & Sawang, ). Organizational leaders should take note of this finding because men and women might need different resources and types of support when facing work‐related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…Another important implication that is apparent in these results is that men and women cope with work stressors in different ways. As predicted by social role theory (Eagly, ), it appears that society places pressure on both men and women to cope with stressors in different ways (e.g., Feingold, ; Watson, Goh, & Sawang, ). Organizational leaders should take note of this finding because men and women might need different resources and types of support when facing work‐related stressors.…”
Section: Discussionmentioning
confidence: 99%
“…We considered participants' age and gender as possible covariates because previous research has shown that these variables are related to work stress (Barnes‐Farrell, Rumery, & Swody, ; Rauschenbach, Krumm, Thielgen, & Hertel, ; Watson, Goh, & Sawang, ).…”
Section: Methodsmentioning
confidence: 99%
“…Control Variables. We considered participants age and gender as possible covariates because previous research has shown that these variables are related to work stress (Barnes-Farrell, Rumery, & Swody, 2002;Rauschenbach, Krumm, Thielgen, & Hertel, 2013;Watson, Goh, & Sawang, 2011). Table 1 provides descriptive statistics and intercorrelations for all study variables.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, by using a single item measure of stress, differences in sources of stress among respondents are not reflected. For example, some studies note that men and women may be affected and appraise stressors differently [70,71].…”
Section: Limitationsmentioning
confidence: 99%